2021
DOI: 10.1007/s00417-021-05361-3
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of three different antiseptic ophthalmic preparations as surgical prophylaxis

Abstract: Purpose In the era of antibiotic resistance, there is an increased interest in antiseptic solutions that might represent a reliable option for ocular surface disinfection. The objective of this study is to compare for the first time three different antiseptic ophthalmic preparations to assess their in vitro antimicrobial activity. Methods The antiseptic activity of three commercial ophthalmic solutions, IODIM (povidone-iodine 0.6% in hyaluronic acid vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
6
1
2
Order By: Relevance
“…According to the results, each formulation prevents bacterial growth once challenged, with the exception of Dropsept, which was not able to limit P. aeruginosa. Our data are not in line with Tognetto et al (2022), who published a microbicidal effect only for Iodim [40].…”
Section: Discussioncontrasting
confidence: 99%
“…According to the results, each formulation prevents bacterial growth once challenged, with the exception of Dropsept, which was not able to limit P. aeruginosa. Our data are not in line with Tognetto et al (2022), who published a microbicidal effect only for Iodim [40].…”
Section: Discussioncontrasting
confidence: 99%
“…Dropsept (Iromed Group s.r.l, Rome, Italy), a new preparation based on CHX 0.02%, Vitamin E and D-a-Tocopherol polyethylene glycol 1000 succinate, was recently introduced. An in vitro study by Tognetto et al showed a good antiseptic activity against E. coli, a weaker activity against the staphylococci strains and P. aeruginosa, while Candida albicans was not affected [49]. Similar in vitro results were shown by Caruso et al, with effective bactericidal activity on S. aureus, S. epidermidis, and Escherichia coli, but with no inhibitory effect on the growth of P. aeruginosa.…”
Section: Chlorhexidine (Chx)mentioning
confidence: 56%
“…Again in vitro, Tognetto et al showed antimicrobial efficacy of Ozodrop against S. epidermidis, E. coli, and P. aeruginosa. Moreover, no activity was detected against S. aureus strains and C. albicans [49]. Focusing on the anti-Candida effect, Celenza et al showed an antifungal effect on several Candida species [65].…”
Section: Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it promotes the release of growth factors promoting wound healing, such as PDGF and TGF-β, and collagen synthesis. However, ozone alone cannot be used in otological preparations, as it would cause irritation of the mucous membranes of the ear [34]. On the contrary, the combination with liposomes, which are spherical vesicular structures in aqueous suspension made up of phospholipids organized in a bilayer, stabilizes ozone and makes it tolerated by the ear surface.…”
Section: Discussionmentioning
confidence: 99%